IMPLEMENTASI PENDIDIKAN PROGRESIVISME SEBAGAI INOVASI PEMBELAJARAN MEMBACA KITAB KUNING DI PESANTREN DARUSSOLAH AN-NAWAWIYAH BANGKALAN - Takwallo, Takwallo (TA'LIM : Jurnal Studi Pendidikan Islam, 2025)
Islamic boarding school educational institutions in Indonesia are identical. This study aims to capture learning innovations and implementation of progressive education in the Independent Book Reading Guidance (BMKM) program at the Darussolah An-Nawawiyah Pakong Bangkalan Islamic Boarding School. Using a field-based qualitative research method. The author found two things, first the BMKM learning innovation combines the sorongan and baht masā'il methods so that there is independence and equality between students. The second innovation lies in learning outcomes that not only emphasize the ability to read yellow books but also understand their contents, and the ability to write, translate them, and convey this understanding, therefore the books used are books that can increase Islamic insight including fiqh, morals, and aqidah. The second finding is that BMKM implements progressive education based on three indicators, namely the pragmatism of BMKM participants preparing all means to achieve learning goals, the second aspect is experimentalism, namely involving students in almost the entire learning process, the task of the mentor is only to direct and motivate. The third aspect, individualism, is where the tutor directs students to which aspects of their learning achievements, which include reading books, conveying understanding, and writing translations, must be honed and developed.